1988
DOI: 10.1002/1097-0142(19880915)62:6<1215::aid-cncr2820620629>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of survival in children with medulloblastoma and cerebellar astrocytoma

Abstract: To determine the quality of survival for children with posterior fossa tumors, comprehensive neuropsychological, behavioral, and academic assessment and physician ratings of functional status were obtained on 15 brain tumor patients (ages 6-19 years) at a median of 20 months post-diagnosis. More than 50% of the children (whether irradiated or not) experienced major problems in academic, motor, sensory, cognitive, and emotional function. All but two children were reported by teachers to be "slow workers," and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 12 publications
2
33
0
2
Order By: Relevance
“…The literature shows that childhood brain tumors below the tentorium bring a risk of cognitive morbidity, affecting a variety of higher cognitive functions. While MBs have the greater risk of neuropsychological impairment, non-malignant cerebellar tumors are also associated with motor, intellectual, and specific cognitive deficits [6,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature shows that childhood brain tumors below the tentorium bring a risk of cognitive morbidity, affecting a variety of higher cognitive functions. While MBs have the greater risk of neuropsychological impairment, non-malignant cerebellar tumors are also associated with motor, intellectual, and specific cognitive deficits [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…Later research has supported the claim of progressive intellectual deterioration in radiated MB survivors [15,27,29,38,39]. Fortytwo percent of radiated MB survivors had intellectual deficits at 5 years post-treatment and 80% showed these deficits at 10 years post-treatment [27].…”
Section: Time Since Treatmentmentioning
confidence: 91%
See 1 more Smart Citation
“…9,12,14,18,20 Other previous studies have reported discrepant findings that may be attributable to heterogeneity with respect to participant age, tumor location, and interval from diagnosis or attrition bias. 2,11,41,42 The importance to HRQoL of neurological deficit, the functional consequences of which were captured in the motor and sensory function domain, was reflected in the predictive role of that domain by parent-report.…”
Section: Bull Et Al: Predictors Of Hrqol In Children With Cerebellarmentioning
confidence: 93%
“…Poorer HRQoL has been associated with factors such as low IQ 11,12 and poor social, 9 physical, 13,14 behavioral, 11 and emotional functioning.…”
mentioning
confidence: 99%